Chondroitin sulfate proteoglycan is a potential target of memantine to improve cognitive function via the promotion of adult neurogenesis. (28th July 2022) - Maeda, Shoichiro; Yamada, Jun; Iinuma, Kyoko M.; Nadanaka, Satomi; Kitagawa, Hiroshi; Jinno, Shozo
Abstract : Background and Purpose: Chondroitin sulfate proteoglycan (CSPG) constitutes the neurogenic niche in the hippocampus. The reduction of hippocampal neurogenesis is involved in ageing‐related cognitive decline and dementia. The purpose of this study is to find candidates that improve cognitive function by analysing the effects of memantine (MEM), a therapeutic agent for Alzheimer's disease, on CSPG and adult hippocampal neurogenesis. Experimental Approach: The effects of MEM on neurogenesis‐related cells and CSPG content were assessed in the hippocampus of middle‐aged mice. The MEM‐induced alterations in gene expressions of neurotrophins and enzymes associated with biosynthesis and degradation of CSPG in the hippocampus also were measured. The effects of MEM on cognitive function were estimated using a behavioural test battery. The same set of behavioural tests was applied to evaluate the effects of pharmacological depletion of CSPG in the hippocampus. Key Results: The densities of newborn granule cells and content of CSPG in the hippocampus were increased by MEM. The expression levels of the enzyme responsible for the biosynthesis CSPG were increased by MEM. The neurotrophin‐related molecules were activated by MEM. Short‐ and long‐term memory performance was improved by MEM. Pharmacological depletion of CSPG impairs the effects of MEM on cognitive improvement in middle‐aged mice. Conclusion and Implications: MEM regulates the biosynthesis and degradation of CSPG, which may underlie the improvement of cognitive function via the promotion of adult hippocampal neurogenesis. These results imply that CSPG‐related enzymes potentially may be attractive candidates for the treatment of ageing‐related cognitive decline.